2003
DOI: 10.1074/jbc.m301684200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of the Non-coding RNA DsrA and RpoS mRNA with the 30 S Ribosomal Subunit

Abstract: Expression ofs , the gene product of rpoS, is controlled translationally in response to many environmental stresses. DsrA, a small 87-nucleotide non-coding RNA molecule, acts to increase translational efficiency of RpoS mRNA under some growth conditions. In this work, we demonstrate that DsrA binds directly to the 30 S ribosomal subunit with an observed equilibrium affinity of 2.8 ؋

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 39 publications
(79 reference statements)
1
19
0
Order By: Relevance
“…A recent in vivo analysis [124] suggested the following mechanistic model: Hfq associates with the helicase CsdA and binds to an A-rich sequence in the leader of rpoS, allowing the annealing of DsrA to rpoS and efficient translation. Nevertheless, Hfq binding does not seem to be necessary for the interaction of rpoS and DsrA with 30S [125]. The same group showed using photochemical crosslinking that the r-protein S1 interacts with both RNAs on the 30S [126] and suggested that S1 might play a role in facilitating translation of sRNA regulated mRNAs.…”
Section: Dsra/rpos Translation Activationmentioning
confidence: 89%
“…A recent in vivo analysis [124] suggested the following mechanistic model: Hfq associates with the helicase CsdA and binds to an A-rich sequence in the leader of rpoS, allowing the annealing of DsrA to rpoS and efficient translation. Nevertheless, Hfq binding does not seem to be necessary for the interaction of rpoS and DsrA with 30S [125]. The same group showed using photochemical crosslinking that the r-protein S1 interacts with both RNAs on the 30S [126] and suggested that S1 might play a role in facilitating translation of sRNA regulated mRNAs.…”
Section: Dsra/rpos Translation Activationmentioning
confidence: 89%
“…The 30S ribosomal subunit was purified from E. coli as described previously (41). lig RNA transcripts were synthesized with T7 RNA polymerase from PCR products by using procedures described previously (35). The template for the PCR was plasmid pRAT659, which harbored a lig=-=bglB fusion.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of RNA can be influenced by ionic concentrations. For example, the accessibility of the RBS of the E. coli rpoS transcript is sensitive to magnesium concentration changes in vitro, indicating that conformational changes in the mRNA leader may facilitate osmotic regulation of rpoS (35). Additionally, the melting point of the Salmonella fourU thermometer is altered by shifts in magnesium concentrations within a physiological range (36).…”
mentioning
confidence: 99%
“…The procedure was carried out with cells grown to early stationary phase or with cells exposed to human serum (see Methods) to mimic systemic PAO1 infection (Van Delden, 2004). The protocol used here deviates from the coimmunoprecipitation of sRNA with Hfq antibodies from cell lysates (Zhang et al, 2003), and is biased against sRNAs that eventually associate with ribosomes (Worhunsky et al, 2003).…”
Section: Identification Of Ncrnas and Srna Candidates By Rnomicsmentioning
confidence: 99%